2024
DOI: 10.3390/s24082557
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Height and Exposure in Multispectral Vegetation Index Response and Product Characteristics in a Traditional Olive Orchard

Carolina Perna,
Andrea Pagliai,
Riccardo Lisci
et al.

Abstract: The present research had two aims. The first was to evaluate the effect of height and exposure on the vegetative response of olive canopies’ vertical axis studied through a multispectral sensor and on the qualitative and quantitative product characteristics. The second was to examine the relationship between multispectral data and productive characteristics. Six olive plants were sampled, and their canopy’s vertical axis was subdivided into four sectors based on two heights (Top and Low) and two exposures (Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In precision oliviculture, some studies have shown that the variability observed in olive production was closely linked to soil variability, in particular to the concentration of organic matter, nitrogen and electrical conductivity [6,7]. Scientific research has focused on the study of biophysical [8,9] and spectral parameters [10,11] to achieve a better understanding of the physiological state, vegetative vigour and productivity of plants. The main biophysical canopy parameters currently observed include canopy height (CH), canopy area (CA), canopy volume (CV) and, in some cases, canopy perimeter and penetrability [8,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In precision oliviculture, some studies have shown that the variability observed in olive production was closely linked to soil variability, in particular to the concentration of organic matter, nitrogen and electrical conductivity [6,7]. Scientific research has focused on the study of biophysical [8,9] and spectral parameters [10,11] to achieve a better understanding of the physiological state, vegetative vigour and productivity of plants. The main biophysical canopy parameters currently observed include canopy height (CH), canopy area (CA), canopy volume (CV) and, in some cases, canopy perimeter and penetrability [8,12,13].…”
Section: Introductionmentioning
confidence: 99%